Transient Receptor Potential Vanilloid Subtype 1: Potential Role in Infection, Susceptibility, Symptoms and Treatment of COVID-19 - Liviero, Filippo; Campisi, Manuela; Mason, Paola; Pavanello, Sofia (Frontiers in Medicine, 2021)
The battle against the new coronavirus that continues to kill millions of people will be still long. Novel strategies are demanded to control infection, mitigate symptoms and treatment of COVID-19. This is even more imperative given the long sequels that the disease has on the health of the infected. The discovery that S protein includes two ankyrin binding motifs (S-ARBMs) and that the transient receptor potential vanilloid subtype 1 (TRPV-1) cation channels contain these ankyrin repeat domains (TRPs-ARDs) suggest that TRPV-1, the most studied member of the TRPV channel family, can play a role in binding SARS-CoV-2. This hypothesis is strengthened by studies showing that other respiratory viruses bind the TRPV-1 on sensory nerves and epithelial cells in the airways. Furthermore, the pathophysiology in COVID-19 patients is similar to the effects generated by TRPV-1 stimulation. Lastly, treatment with agonists that down-regulate or inactivate TRPV-1 can have a beneficial action on impaired lung functions and clearance of infection. In this review, we explore the role of the TRPV-1 channel in the infection, susceptibility, pathogenesis, and treatment of COVID-19, with the aim of looking at novel strategies to control infection and mitigate symptoms, and trying to translate this knowledge into new preventive and therapeutic interventions.